Tūayāng kānčhat kānrīanrū phư̄a sœ̄msāng ʻuppanisai "phō̜phīang" (Mūnnithi Sayām Kammačhon, 2015)
On education development in Thailand by implementing sufficiency economy philosophy using learning activities in school.